2008
DOI: 10.1109/mcas.2008.916097
|View full text |Cite
|
Sign up to set email alerts
|

Insect-vision inspired collision warning vision processor for automobiles

Abstract: FeatureDigital Object Identifier 10. 1109 /MCAS.2008 Vision is expected to play important roles for car safety enhancement. Imaging systems can be used to enlarging the vision field of the driver. For instance capturing and displaying views of hidden areas around the car which the driver can analyze for safer decision-making. Vision systems go a step further. They can autonomously analyze the visual information, identify dangerous situations and prompt the delivery of warning signals. For instance in case of r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
2
2
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…Another technique was learned from Locusta Migratoria, where the speed and direction of the edge displacements in the projected image are measured, and if they exceed a certain threshold, the sensor detects the approaching object . The method was deeply analyzed and even a special purpose approaching object detector chip was designed , in the framework of the LOCUST European FP6 project . The chip could generate warning signals before 0.5 to 1 s before a collision in traffic circumstances .…”
Section: Approaching Detector Sensorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another technique was learned from Locusta Migratoria, where the speed and direction of the edge displacements in the projected image are measured, and if they exceed a certain threshold, the sensor detects the approaching object . The method was deeply analyzed and even a special purpose approaching object detector chip was designed , in the framework of the LOCUST European FP6 project . The chip could generate warning signals before 0.5 to 1 s before a collision in traffic circumstances .…”
Section: Approaching Detector Sensorsmentioning
confidence: 99%
“…Extensive neural studies showed that some of the largest neurons in the Locust brain are dedicated to the collision prediction task . After successful identification, measurement, modeling, characterization of this neural circuit, a technical team built and verified a visual sensor‐processor chip for automotive application to detect collision threat applying the same principles that the brain system of the Locust does.…”
Section: Introductionmentioning
confidence: 99%
“…The knowledge of the neural circuitry can be used here to construct artificial vision systems for DSA. (Cembrano, et al, 2008) Natural vision systems have been improved through millennia of evolution and are more robust and efficient than artificial counterparts. Many insects rely on vision to control its own movements and observe that of others around it.…”
Section: Biological Models For Dsamentioning
confidence: 99%
“…As it turned out, some of the largest neurons in the Locust brain are dedicated to this task [1]. After successful identification, measurement, modeling, characterization of this neural circuit of the locust, a technical team built and verified a visual sensor-processor chip for automotive application, which could detect collision threat [2] applying the same principles what the brain system of the Locust does.…”
Section: Introductionmentioning
confidence: 99%
“…Other advantage of the looming sensor device is that it makes possible to predict the architecture of a higher level neural circuit, which evaluate the output of the modeled ganglion cells. In the future, the continuation of these studies may lead to a micro sensor devicessimilar to the mentioned Locust collision warning chip [2] -which can call the attention to approaching objects.…”
Section: Introductionmentioning
confidence: 99%